The relationship between positron emission tomography-computed tomography imaging and histopathological features of thyroid incidentalomas detected during follow-up for primary malignancy - Ustaalıoğlu Öven, Başak; Kılıçoğlu, Zeynep Gamze; Bilici, Ahmet Erkan; Tato?lu, Mehmet Tarık; Canberk, Şule; Tilki, Metin; Aker Vardar, Fügen (Wolters Kluwer Medknow Publications, 2019)
Aim of the Study: While the rate of thyroid incidentaloma detected on positron emission tomography (PET) was reported as 4%, the malignancy rate was 14%u50%. We evaluated the thyroid nodules which were detected by PET-computerized tomography (CT) in cancer patients and analyzed the pathological results of those thyroid nodules diagnosed by fine needle aspiration biopsy (FNAB) and their correlation with the maximum standardized uptake (SUVmax) value and PET imaging features. Materials and Methods: FNAB were performed for 40 thyroid incidentalomas. We analyzed the relationship between the histopathological findings and radiological features by Pearson's correlations and Chi-square-Fisher's exact tests to evaluate the factors associated with SUVmax. Results: The median SUVmax values were 5.4 for thyroid nodules. Totally, 14 malignancies were detected by FNAB (35%).The sensitivity and specificity of SUVmax value for diagnosis of malignancy were 87.5% and 52%, respectively. Positive and negative predictive values were 36.8% and 92.8%. The most common malignant and benign pathologies were classic variant papillary carcinoma and benign colloidal nodule. The median SUVmax was the higher in colon cancer thyroid metastasis and oncocytic neoplasia (SUVmax 14.5 and 13.6, respectively). Histopathological type was not related with nodule size but positively associated with categorical SUVmax(r = 0.318, P = 0.04) and negatively correlated with both the density of the thyroid nodule in PET-CT (r = 0.0042, P = 0.01) and density of nodule in ultrasound (USG) (r = 0.305, P = 0.05). Margin of the thyroid nodule in USG (P = 0.007) and internal component of the nodule in PET (P = 0.03) were found to be important factors to differentiate benign or malignant lesion. Conclusion: If the thyroid nodule is detected with flouro-2-deoxy-D-glucose uptake, to differentiate benign nodule from malignant, cytological examination is noteworthy to diagnose the more aggressive type of thyroid nodule and also thyroid metastasis from primary cancer.
WOS: 000470851300023
PubMed ID: 31169225
Keywords: Biopsy; Malignancy; Positron Emission Tomography-Computerized Tomography; Thyroid Incidentaloma